Method for preparing antibacterial composite coating by filling micropores of micro-arc oxidation titanium alloy plate with nano-Ag / ZSM-5 molecular sieve and antibacterial composite coating
By filling the nano-Ag/ZSM-5 molecular sieve in the holes of the micro-arc titanium oxide alloy plate and sealing the holes, the corrosion problems caused by the holes of the micro-arc titanium oxide film layer are solved, the wear resistance, corrosion resistance and antibacterial properties of the titanium alloy plate are improved, and its service life is extended.
Patent Information
- Application Number
- CN202411840430.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-14
AI Technical Summary
In the prior art, the holes or microcracks present in the microarc oxide film layer provide a good mass transfer channel for the penetration, transportation and diffusion of corrosive media in the environment, resulting in the loss of good protection of the ceramic film layer and affecting the corrosion resistance of titanium alloy materials.
The pores of the microarc titanium oxide alloy plate were filled and sealed by nano-arc Ag/ZSM-5 molecular sieve. The nano-ZSM-5 molecular sieve was prepared by in-situ hydrothermal synthesis, and Ag was loaded by ion exchange method, and finally the antibacterial composite coating was formed by secondary hydrothermal sealing.
It improves the mechanical strength and antibacterial properties of titanium alloy plates, reduces the maintenance and use costs of marine engineering facilities, and extends the service life of titanium alloy materials.
Smart Images

Figure CN119615161A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of antibacterial composite coatings, and relates to a method for preparing an antibacterial composite coating by filling micropores of a micro-arc oxidation titanium alloy plate with nano-Ag / ZSM-5 molecular sieve, and the antibacterial composite coating. Background Art
[0002] Titanium alloy has become an ideal material for marine equipment due to its many advantages such as low density, high specific strength, low magnetism and good corrosion resistance. There are a large number of bacteria and other microorganisms in seawater. These microorganisms will adhere to the surface of titanium alloy, continue to multiply and secrete some sticky substances, and then form a biological fouling layer. This fouling layer will increase the roughness of the equipment surface and change its fluid mechanics properties. It will also cause wear during operation, destroy its original structural integrity, and reduce its strength and other properties. At the same time, the tiny wounds produced during the wear process are easy to become the starting point of corrosion, accelerating the corrosion process of titanium alloy in seawater, and further affecting the normal use and life of the equipment.
[0003] Micro-arc oxidation (MAO) is a new technology that directly grows a ceramic layer in situ on the surface of aluminum, magnesium, titanium and their alloys to modify the surface of non-ferrous metals. The use of micro-arc oxidation technology to treat titanium alloys can significantly improve their wear resistance and corrosion resistance. However, there are a large number of micron-sized holes or microcracks in the micro-arc oxidation film, which provides a good mass transfer channel for the penetration, transportation and diffusion of corrosive media in the environment, and makes it possible for material corrosion behavior to occur, resulting in the ceramic film losing good protection. Summary of the invention
[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing an antibacterial composite coating by filling the micropores of a micro-arc oxidation titanium alloy plate with nano-Ag / ZSM-5 molecular sieve and an antibacterial composite coating. The nano-Ag / ZSM-5 molecular sieve is used to fill and seal the MAO titanium alloy, which not only improves the mechanical strength of the material, but also improves the antibacterial and antibacterial properties, thereby solving the technical problem that the holes or microcracks in the micro-arc oxidation film layer in the prior art provide a good mass transfer channel for the penetration, transportation and diffusion of corrosive media in the environment, which makes it possible for material corrosion behavior to occur, thereby causing the ceramic film layer to lose good protection.
[0005] In order to achieve the above object, the present invention adopts the following technical solution: The invention provides a method for preparing an antibacterial composite coating by filling micropores of a micro-arc oxidized titanium alloy plate with nano-Ag / ZSM-5 molecular sieve. The method comprises the following steps: pretreating the surface of the titanium alloy plate by micro-arc oxidation technology, preparing nano-ZSM-5 molecular sieve grains by in-situ hydrothermal synthesis, loading Ag on the nano-ZSM-5 molecular sieve by an ion exchange method to obtain a nano-Ag / ZSM-5 molecular sieve, filling the nano-Ag / ZSM-5 molecular sieve in the pores of the titanium alloy plate after micro-arc oxidation, and performing secondary hydrothermal sealing on the filled titanium alloy plate to obtain the antibacterial composite coating.
[0006] Further, the titanium alloy plate is polished, and the polished titanium alloy plate is washed, dried, and subjected to micro-arc oxidation treatment to deposit an oxide film layer on the surface and remove surface dirt; The gel solution is placed in a reactor, subjected to a hydrothermal reaction in an oven, and nano ZSM-5 molecular sieve crystals are obtained by washing and drying. The nano ZSM-5 zeolite molecular crystal powder is dissolved in deionized water, ammonium chloride is added, and the temperature is raised and stirred to obtain NH4-ZSM-5 molecular sieve; the NH4- ZSM-5 molecular sieve is dissolved in deionized water, silver nitrate is added, and the temperature is raised and stirred to obtain nano Ag / ZSM-5 molecular sieve; Adding nano Ag / ZSM-5 molecular sieve into anhydrous ethanol to obtain Ag / ZSM-5 seed solution, drop-coating the Ag / ZSM-5 seed solution on the center of the micro-arc oxidation titanium alloy plate, oscillating until the drop-coated liquid surface covers the surface of the titanium alloy plate, and then washing and drying the surface after oscillation; The dried titanium alloy plate and the mother liquor are placed in a reactor, the titanium alloy plate is immersed in the mother liquor for secondary hydrothermal sealing, and the surface of the titanium alloy plate is repeatedly rinsed with deionized water after crystallization to obtain an antibacterial composite coating.
[0007] Furthermore, the electrolyte for the micro-arc oxidation treatment includes sodium hexametaphosphate, potassium fluoride, sodium sulfide, and sodium molybdate, and the solvent is deionized water; Sodium hexametaphosphate: 12 g / L; Potassium fluoride: 4 g / L; Sodium sulfide: 15 g / L; Sodium molybdate: 5 g / L.
[0008] Furthermore, the gel solution includes tetraethyl orthosilicate, sodium aluminate, tetrapropylammonium hydroxide, and deionized water; the dosage of the tetraethyl orthosilicate, sodium aluminate, tetrapropylammonium hydroxide, and deionized water is SiO2:Al2O3:tetrapropylammonium hydroxide:deionized water=40. 100:1:24:1500 OK.
[0009] Furthermore, the hydrothermal reaction is carried out in an oven, the oven temperature is 220° C., and the hydrothermal reaction time is 24 hours.
[0010] Furthermore, the mother liquor comprises tetraethyl orthosilicate, sodium aluminate, tetrapropylammonium hydroxide and deionized water; the dosage of the tetraethyl orthosilicate, sodium aluminate, tetrapropylammonium hydroxide and deionized water is in the ratio of SiO2:Al2O3:tetrapropylammonium hydroxide:deionized water=40. 100:1:24:2000 OK.
[0011] Further, the heating and stirring to obtain NH4-ZSM-5 molecular sieve was performed at a heating temperature of 80°C and a stirring rate of 500 r / min for 2 hours; the heating and stirring to obtain nano-Ag / ZSM-5 molecular sieve was performed at a heating temperature of 60°C and a stirring rate of 500 r / min for 3 hours.
[0012] Furthermore, the nano ZSM-5 molecular sieve has a grain size of 400 600nm.
[0013] The present invention also provides an antibacterial composite coating, which is prepared based on the above method of preparing the antibacterial composite coating by filling micropores of a micro-arc oxidation titanium alloy plate with nano-Ag / ZSM-5 molecular sieve.
[0014] Furthermore, the antibacterial composite coating is used in harsh marine environments.
[0015] Compared with the prior art, the present invention has the following beneficial technical effects: The present invention discloses a method for preparing an antibacterial composite coating by filling micropores of a micro-arc oxidized titanium alloy plate with nano-Ag / ZSM-5 molecular sieves. The titanium alloy plate after micro-arc oxidation is used as a carrier, the nano-Ag / ZSM-5 molecular sieves are filled in the pores of the titanium alloy plate after micro-arc oxidation by an oscillation method, and the pores are sealed by secondary hydrothermal treatment, thereby improving the performance of the titanium alloy plate and reducing the maintenance cost and use cost of marine engineering facilities.
[0016] The present invention discloses a method for preparing an antibacterial composite coating by filling micropores of a micro-arc oxidation titanium alloy plate with nano-Ag / ZSM-5 molecular sieve. The nano-ZSM-5 molecular sieve has the advantages of good hydrothermal stability, high temperature resistance, corrosion resistance, green environmental protection, and high mechanical strength. + The ZSM-5 molecular sieve material is modified to form a nano-Ag / ZSM-5 molecular sieve, which is then filled into the holes formed by the micro-arc oxidation titanium alloy plate to improve the wear resistance and corrosion resistance of the titanium alloy material.
[0017] The present invention discloses a method for preparing an antibacterial composite coating by filling micropores of a micro-arc oxidized titanium alloy plate with nano-Ag / ZSM-5 molecular sieves, wherein the nano-Ag / ZSM-5 molecular sieves are rigid particles and have antibacterial properties. The micro-arc oxidized titanium alloy and the nano-Ag / ZSM-5 molecular sieves are combined to form an antibacterial composite coating, which gives the titanium alloy plate functionalization, can improve wear resistance and corrosion resistance, and further improve the performance of the titanium alloy plate.
[0018] The invention discloses a method for preparing an antibacterial composite coating by filling micropores of a micro-arc oxidation titanium alloy plate with nano-Ag / ZSM-5 molecular sieve. The reaction conditions are mild, and the prepared composite coating material has a regular morphology and good material stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a scanning electron microscope image of a titanium alloy plate after micro-arc oxidation in an embodiment of the present invention; Figure 2 This is a scanning electron microscope image of nano ZSM-5 molecular sieve grains in an embodiment of the present invention; Figure 3 This is a scanning electron microscope image of nano-Ag / ZSM-5 molecular sieve filled in the pores of a micro-arc oxidation titanium plate in an embodiment of the present invention; Figure 4 This is a scanning electron microscope image of the secondary hydrothermal sealing of the titanium alloy plate in the embodiment of the present invention; Figure 5 This is an energy dispersive spectrometer image of the titanium alloy plate after secondary hydrothermal sealing in an embodiment of the present invention; Figure 6 This is a friction coefficient diagram of a micro-arc oxidation titanium alloy plate and a nano-Ag / ZSM-5 molecular sieve filled antibacterial composite coating in an embodiment of the present invention; Figure 7 It is a potentiodynamic polarization curve diagram of an antibacterial composite coating of the present invention in a 3.5wt.% NaCl solution; Figure 8 This is a test diagram of the antibacterial zone of the nano-Ag / ZSM-5 molecular sieve filled in the titanium alloy plate of the present invention. DETAILED DESCRIPTION
[0020] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0021] Example 1 The present invention discloses a method for preparing an antibacterial composite coating by filling micropores of a micro-arc oxidation titanium alloy plate with nano-Ag / ZSM-5 molecular sieve, comprising the following steps: The surface of the titanium alloy plate was pretreated by micro-arc oxidation technology, and nano ZSM-5 molecular sieve grains were prepared by in-situ hydrothermal synthesis. Ag was loaded on the nano ZSM-5 molecular sieve by ion exchange method to obtain nano Ag / ZSM-5 molecular sieve. The nano Ag / ZSM-5 molecular sieve was filled in the pores of the titanium alloy plate after micro-arc oxidation, and the filled titanium alloy plate was sealed by secondary hydrothermal synthesis.
[0022] Specifically, the surface of the titanium alloy plate is polished with sandpaper, and the polished titanium alloy plate is placed in a micro-arc oxidation electrolyte for micro-arc oxidation treatment to deposit an oxide film layer on the surface of the titanium alloy plate, and then rinsed and dried.
[0023] A 10×10×2mm titanium plate was polished with sandpaper of 400#, 600#, 800#, and 1200# grit in sequence, and the polished titanium alloy plate was placed in a micro-arc oxidation electrolyte, wherein the electrolyte included sodium hexametaphosphate, potassium fluoride, sodium sulfide, and sodium molybdate, and the solvent was deionized water. 12 grams of sodium hexametaphosphate was added to one liter of deionized water, 4 grams of potassium fluoride was added to one liter of deionized water, 15 grams of sodium sulfide was added to one liter of deionized water, and 5 grams of sodium molybdate was added to one liter of deionized water. The micro-arc oxidation treatment time was 15 minutes, so that an oxide film layer was deposited on the surface of the titanium alloy plate, and then it was cleaned to remove surface dirt, and then it was placed in a detergent solution for ultrasonic cleaning for 30 minutes, and then rinsed with deionized water, and placed in a drying oven with the temperature adjusted to 60°C for drying for standby use.
[0024] like Figure 1 As shown in the figure, the titanium alloy plate after micro-arc oxidation has volcanic-shaped micropores, and the size of the micropores is 1 2μm.
[0025] The gel solution is placed in a reactor, subjected to a hydrothermal reaction in an oven, and nano ZSM-5 molecular sieve crystals are obtained by washing and drying.
[0026] Tetraethyl orthosilicate, sodium aluminate, tetrapropylammonium hydroxide and deionized water constitute a gel solution. The dosage of tetraethyl orthosilicate, sodium aluminate, tetrapropylammonium hydroxide and deionized water is as follows: SiO2:Al2O3:tetrapropylammonium hydroxide:deionized water = 40 100:1:24:1500, the synthesized gel solution was transferred into the reactor, and hydrothermally reacted at 220°C in an oven for 24 hours, centrifuged at 5000 rpm for 5 minutes, and washed with ionized water, and the operation was repeated until the pH reached neutrality, that is, the pH neutrality was 7. The nano ZSM-5 molecular sieve crystals were obtained and placed in an oven at 60°C for drying.
[0027] The size of nano ZSM-5 molecular sieve particles is about 500 600nm, if the amount of tetraethyl orthosilicate, sodium aluminate, tetrapropylammonium hydroxide, and deionized water is determined according to SiO2:Al2O3:tetrapropylammonium hydroxide:deionized water=40:1:24:1500, the size of the nano ZSM-5 molecular sieve grains is about 550nm; if the amount of tetraethyl orthosilicate, sodium aluminate, tetrapropylammonium hydroxide, and deionized water is determined according to SiO2:Al2O3:tetrapropylammonium hydroxide:deionized water=100:1:24:1500, the size of the nano ZSM-5 molecular sieve grains is about 580nm; in this embodiment, the amount of tetraethyl orthosilicate, sodium aluminate, tetrapropylammonium hydroxide, and deionized water is determined according to SiO2:Al2O3:tetrapropylammonium hydroxide:deionized water=60:1:24:1500, the size of the nano ZSM-5 molecular sieve grains is about 560nm; Figure 2 As shown, it can be filled in a micro-arc oxidized titanium alloy plate.
[0028] The nano ZSM-5 zeolite molecular crystal powder is dissolved in deionized water, ammonium chloride is added, and the temperature is raised and stirred to obtain NH4-ZSM-5 molecular sieve. The NH4-ZSM-5 molecular sieve is dissolved in deionized water, silver nitrate is added, and the temperature is raised and stirred to obtain nano Ag / ZSM-5 molecular sieve.
[0029] Add nano ZSM-5 molecular sieve to deionized water, mix evenly, add ammonium chloride, heat to 80°C and stir at a stirring rate of 500 r / min for 2 hours, then wash and dry to obtain NH4-ZSM-5 molecular sieve; dissolve NH4-ZSM-5 molecular sieve in deionized water, add silver nitrate, heat to 60°C, stir at a stirring rate of 500 r / min for 3 hours, then centrifuge and dry to obtain nano Ag / ZSM-5 molecular sieve.
[0030] Nano-Ag / ZSM-5 molecular sieves were added into anhydrous ethanol to obtain Ag / ZSM-5 seed solution, and the Ag / ZSM-5 seed solution was drop-coated on the center of the micro-arc oxidation titanium alloy plate until the drop-coated liquid surface covered the surface of the titanium alloy plate and then oscillated, and then the surface was rinsed and dried after oscillation.
[0031] Nano-Ag / ZSM-5 molecular sieves were filled into the holes of the micro-arc oxidation titanium alloy plate by oscillation method. 0.1g of nano-Ag / ZSM-5 molecular sieves were weighed and added to 10g of anhydrous ethanol, and ultrasonicated for 30 minutes to make it evenly dispersed to obtain a 1% mass fraction of Ag / ZSM-5 seed solution. The oscillator frequency was 120rpm and the oscillation time was 60min.
[0032] Use a pipette to take 20 μ1. 1% Ag / ZSM-5 seed solution was dripped on the center of the titanium alloy plate and shaken until the liquid surface covered the surface of the titanium alloy plate and stopped dripping. After shaking for 60 minutes, the surface was rinsed clean and dried at 60℃ overnight for later use.
[0033] like Figure 3 As shown, nano-Ag / ZSM-5 molecular sieve is filled in the pores of the micro-arc oxidation titanium alloy plate.
[0034] The dried titanium alloy plate and the mother liquor are placed in a reactor, the titanium alloy plate is immersed in the mother liquor for secondary hydrothermal sealing, and the surface of the titanium alloy plate is repeatedly rinsed with deionized water after crystallization to obtain an antibacterial composite coating.
[0035] The filled titanium alloy plate was hydrothermally sealed by the secondary hydrothermal growth method. The dried titanium metal plate was placed at the bottom of the reactor. The mother liquor of ethyl orthosilicate, sodium aluminate, tetrapropylammonium hydroxide, and deionized water were used in the ratio of SiO2:Al2O3:tetrapropylammonium hydroxide:deionized water = 60:1:24:2000 for secondary hydrothermal sealing, and crystallized at 120°C for 3h. After the crystallization, the surface of the titanium alloy plate was repeatedly rinsed with deionized water, and finally placed in a 60°C oven for 24h to obtain a composite antibacterial coating.
[0036] The SEM images and EDS element distribution diagrams of the composite coating after secondary hydrothermal sealing are shown in Figure 4 , Figure 5 As shown, from Figure 4 It can be seen that after the secondary hydrothermal synthesis, the nano-Ag / ZSM-5 molecular sieve grows in the micropores of the micro-arc oxidation titanium sheet, achieving the purpose of sealing the pores. Figure 5 It can be seen that the Ag element is detected in the figure, indicating that the Ag element is successfully filled into the holes of the micro-arc oxidation titanium alloy plate, and the Ag element is evenly distributed. Compared with other elements, the Ag element has a lower density, indicating that the content of the incorporated Ag element is low. In addition, Si, Al, O and other elements are detected, with a relatively uniform distribution and a high density, indicating successful incorporation.
[0037] In summary, the titanium alloy plate after micro-arc oxidation is used as the substrate. +The modified nano-Ag / ZSM-5 molecular sieve is filled into the micropores formed by the micro-arc oxidation titanium alloy plate by the oscillation method, and finally the pores are completely sealed by secondary hydrothermal treatment, thereby improving the performance of the titanium alloy plate, which is of great significance for the preparation of environmentally friendly marine antifouling coating materials. This method has mild reaction conditions and good stability. The prepared composite coating material has a regular morphology and good material stability. It is an ideal marine antifouling material. Nano-ZSM-5 molecular sieve has the advantages of good hydrothermal stability, high temperature resistance, corrosion resistance, green environmental protection, and high mechanical strength. Use Ag + The nano ZSM-5 molecular sieve material is modified to form a nano Ag / ZSM-5 molecular sieve, which is then filled into the micropores formed by the micro-arc oxidation titanium plate to improve the wear resistance and corrosion resistance of the titanium alloy material.
[0038] Example 2 The friction and wear performance of the composite coating of the micro-arc oxidation titanium alloy plate at room temperature was tested using an HT-600 high temperature friction and wear tester. The grinding material was a GCr15 steel ball with a diameter of 6 mm, a dynamic load of 3 N, a rotation speed of 50 r / min, and a grinding time of 1200 s. Figure 6 The figure shows the friction coefficient of the micro-arc oxidized titanium alloy plate and the composite coating filled with nano-Ag / ZSM-5 molecular sieve. It can be seen that the friction coefficient of the composite coating filled with nano-Ag / ZSM-5 molecular sieve is smaller. This is because the nano-Ag / ZSM-5 molecular sieve particles fill the micropores, that is, the cavities, and participate in the formation of the film layer. In addition, the mechanical properties of the nano-Ag / ZSM-5 molecular sieve itself can improve the wear resistance of the film layer, so the wear resistance of the composite coating after filling is better.
[0039] Example 3 The corrosion resistance of the composite coating of micro-arc oxidation titanium alloy plate was tested using the CHI660E electrochemical workstation. The test system is a three-electrode system, including a saturated calomel electrode, a platinum electrode and a sample as the reference electrode, auxiliary electrode and working electrode respectively. The corrosion solution is a 3.5wt% NaCl solution, and the corrosion test is mainly a potentiodynamic polarization curve test. In order to obtain a stable open circuit potential before the test, the test sample was immersed in a 3.5wt.% NaCl solution for 24 hours. According to the open circuit potential of the sample, the potential range of the polarization curve test was selected. According to the potentiodynamic polarization curve, the corrosion potential (Ecorr) and corrosion current density (Icorr) were obtained by the Tafel extrapolation method. Figure 7The figure shows the potentiodynamic polarization curves of pure micro-arc oxidized titanium alloy plate and nano-Ag / ZSM-5 filled micro-arc oxidized titanium alloy plate coating in 3.5wt.% NaCl solution. From the Tafel curve, it can be seen that the corrosion current after nano-ZSM-5 molecular sieve filling is nearly four orders of magnitude smaller than that of pure MAO titanium plate, and the corrosion potential also moves positively by nearly 200mv. This shows that the titanium material filled with nano-ZSM-5 molecular sieve nanoparticles has better corrosion resistance. The pure micro-arc oxidized titanium plate in the figure is the abbreviation of pure micro-arc oxidized titanium alloy plate.
[0040] Example 4 The antibacterial properties of the composite coating of micro-arc oxidation titanium alloy plate were evaluated by the inhibition zone method using inactivated Staphylococcus aureus. Peptone, yeast extract and NaCl were added to 500 mL of distilled water, and then the pH value of the solution was adjusted to 7.0 to prepare LB medium (Luria-Bertani medium). Subsequently, the bacterial solution was prepared, and the samples, culture medium and glassware required for the experiment were sterilized at high temperature. Add 1 mL of Staphylococcus aureus solution to the sterilized culture dish, and then add LB medium, 20 mL per culture dish. Gently shake the culture dish to mix evenly, place it flat on the clean bench, and after the agar solidifies, place the sample in the center of the plate and culture it in a constant temperature incubator at 37°C for 24 hours to observe the size of the inhibition zone. Figure 8 As shown, Figure (a) is the blank control group; Figure (b) is the nano ZSM-5 molecular sieve filling without Ag+ modification; Figures (c), (d), (e), and (f) are titanium alloy plate composite coatings with Ag+ exchange amounts of 0.01mol / L, 0.02mol / L, 0.03mol / L, and 0.04mol / L, respectively. It can be seen from the figures that the titanium alloy plate composite coating has good antibacterial properties, and there is no obvious change between the Ag+ exchange amounts of 0.03mol / L, 0.04mol / L and 0.02mol / L, so the Ag+ exchange amount of 0.02mol / L is better.
[0041] Example 5 The antibacterial composite coating of the present invention is prepared by the method of preparing the antibacterial composite coating by filling the micropores of the micro-arc oxidation titanium alloy plate with nano-Ag / ZSM-5 molecular sieve, and is applied to the harsh marine environment. The antibacterial composite coating not only has excellent corrosion resistance, but also has strong antibacterial ability, which is of great significance for maintaining the safety of marine facilities and extending the service life.
[0042] In the description of the present application, it should be understood that the terms "center", "longitudinal", "lateral", "up", "down", "front", "back", "left", "right", "top", "bottom", "inside", "outside", "axial", "radial", "circumferential", etc., indicating orientations or positional relationships, are based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present invention.
[0043] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.
Claims
1. A method for preparing an antibacterial composite coating by filling micropores of a micro-arc oxidation titanium alloy plate with nano-Ag / ZSM-5 molecular sieve, characterized in that: The following steps are involved: The surface of the titanium alloy plate was pretreated by micro-arc oxidation technology, and nano ZSM-5 molecular sieve grains were prepared by in-situ hydrothermal synthesis. Ag was loaded on the nano ZSM-5 molecular sieve by ion exchange method to obtain nano Ag / ZSM-5 molecular sieve. The nano Ag / ZSM-5 molecular sieve was filled in the pores of the titanium alloy plate after micro-arc oxidation. The filled titanium alloy plate was sealed by secondary hydrothermal method to obtain an antibacterial composite coating.
2. The method for preparing an antibacterial composite coating by filling micropores of a micro-arc oxidation titanium alloy plate with nano-Ag / ZSM-5 molecular sieve according to claim 1, characterized in that: The following steps are involved: The titanium alloy plate is polished, and the polished titanium alloy plate is washed, dried, and subjected to micro-arc oxidation treatment to deposit an oxide film layer on its surface and remove surface dirt; The gel solution is placed in a reactor, subjected to a hydrothermal reaction in an oven, and nano ZSM-5 molecular sieve crystals are obtained by washing and drying. The nano ZSM-5 zeolite molecular crystal powder is dissolved in deionized water, ammonium chloride is added, and the temperature is raised and stirred to obtain NH4-ZSM-5 molecular sieve; the NH4-ZSM-5 molecular sieve is dissolved in deionized water, silver nitrate is added, and the temperature is raised and stirred to obtain nano Ag / ZSM-5 molecular sieve; Adding nano Ag / ZSM-5 molecular sieve into anhydrous ethanol to obtain Ag / ZSM-5 seed solution, drop-coating the Ag / ZSM-5 seed solution on the center of the micro-arc oxidation titanium alloy plate, oscillating until the drop-coated liquid surface covers the surface of the titanium alloy plate, and then washing and drying the surface after oscillation; The dried titanium alloy plate and the mother liquor are placed in a reactor, the titanium alloy plate is immersed in the mother liquor for secondary hydrothermal sealing, and the surface of the titanium alloy plate is repeatedly rinsed with deionized water after crystallization to obtain an antibacterial composite coating.
3. The method for preparing an antibacterial composite coating by filling micropores of a micro-arc oxidation titanium alloy plate with nano-Ag / ZSM-5 molecular sieve according to claim 2, characterized in that: The electrolyte for micro-arc oxidation treatment includes sodium hexametaphosphate, potassium fluoride, sodium sulfide, and sodium molybdate, and the solvent is deionized water; Sodium hexametaphosphate: 12 g / L; Potassium fluoride: 4 g / L; Sodium sulfide: 15 g / L; Sodium molybdate: 5 g / L.
4. The method for preparing an antibacterial composite coating by filling micropores of a micro-arc oxidation titanium alloy plate with nano-Ag / ZSM-5 molecular sieve according to claim 2, characterized in that: The gel solution comprises tetraethyl orthosilicate, sodium aluminate, tetrapropylammonium hydroxide and deionized water; The amount of the tetraethyl orthosilicate, sodium aluminate, tetrapropylammonium hydroxide and deionized water is SiO2:Al2O3:tetrapropylammonium hydroxide:deionized water=40. 100:1:24:1500 OK.
5. The method for preparing an antibacterial composite coating by filling micropores of a micro-arc oxidation titanium alloy plate with nano-Ag / ZSM-5 molecular sieve according to claim 2, characterized in that: The hydrothermal reaction is carried out in an oven at a temperature of 220° C. and a hydrothermal reaction time of 24 hours.
6. The method for preparing an antibacterial composite coating by filling micropores of a micro-arc oxidation titanium alloy plate with nano-Ag / ZSM-5 molecular sieve according to claim 2, characterized in that: The mother liquor comprises tetraethyl orthosilicate, sodium aluminate, tetrapropylammonium hydroxide and deionized water; The amount of the tetraethyl orthosilicate, sodium aluminate, tetrapropylammonium hydroxide and deionized water is SiO2:Al2O3:tetrapropylammonium hydroxide:deionized water=40. 100:1:24:2000 OK.
7. The method for preparing an antibacterial composite coating by filling micropores of a micro-arc oxidation titanium alloy plate with nano-Ag / ZSM-5 molecular sieve according to claim 2, characterized in that: The heating and stirring are performed to obtain NH4-ZSM-5 molecular sieve, the heating temperature is 80°C, and the stirring rate is 500r / min for 2h; The nano Ag / ZSM-5 molecular sieve was obtained by heating and stirring at a temperature of 60° C. and stirring at a stirring rate of 500 r / min for 3 h.
8. The method for preparing an antibacterial composite coating by filling micropores of a micro-arc oxidation titanium alloy plate with nano-Ag / ZSM-5 molecular sieve according to claim 1, characterized in that: The nano ZSM-5 molecular sieve has a grain size of 400 600nm.
9. An antibacterial composite coating, characterized in that: The antibacterial composite coating is prepared by the method for preparing the antibacterial composite coating by filling the micropores of a micro-arc oxidation titanium alloy plate with nano-Ag / ZSM-5 molecular sieve as described in any one of claims 1 to 8.
10. The antibacterial composite coating according to claim 9, characterized in that: The antibacterial composite coating is used in harsh marine environments.